EFFECT OF STIMULATORS AND SILICON COMPLEX FERTILIZERS ON THE PLACEMENT OF FIRST POD OF SOYBEAN VARIETIES - Kamalova Nuriya Shamilevna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article presents data on the effect of separate and combined application of stimulants and silicon complex fertilizers on soybean varieties on their height of the first pod. It was found that stimulants and silicon complex fertilizers had a good effect on the number of height of the first pod, and in both varieties, the height of the first pod was higher when using Maltamin from the stimulants, when comparing stimulants with silicon complex fertilizer, and when using stimulants with silicon complex, silicon complex fertilizer + Maltamin was taken highest placement of the first pod.